The Influence Of Stress And Anxiety Levels On Tiktok Content Consumption In Adolescents And Early Adults - Zulvania, Novelia Salsa; Ahya, Awaludin; Wibowo, Moersito Wimbo (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the effect of stress and anxiety levels on TikTok consumption among respondents. The method used is a quantitative approach with multiple linear regression analysis techniques. The results of the validity test show that all items in the Stress Level (X1), Anxiety (X2), and TikTok Consumption (Y) variables are valid, indicated by a p-value 0.05. The reliability test also showed very good results with Cronbach's Alpha values of 0.919 (X1), 0.971 (X2), and 0.898 (Y), respectively, which means that all research instruments are reliable. The classical assumption test shows that the regression model meets the assumption of normality, there is no multicollinearity, and there is no heteroscedasticity. The results of the regression analysis produce the equation Y = 29.633 + 0.515X1 - 0.132X2 + e. The partial test (t-test) shows that both independent variables have a significant effect on TikTok consumption, with a significance value 0.05. The simultaneous test (F test) also shows that both variables together have a significant effect on TikTok consumption. The coefficient of determination (R²) value of 0.351 indicates that 35.1% of the variability in TikTok consumption can be explained by stress and anxiety levels. This finding indicates that the higher the level of stress and anxiety, the higher the tendency of a person to consume TikTok.